If You Give a Cat ba Cupcake - Numeroff, Laura; Bond, Felicia (USA, 2008)
A series of increasingly far-fetched events might occur if someone wereb to give a cupcake to a cat...
Keywords: Animal Story; Concepts; Juvenile Fiction